PENGEMBANGAN STRATEGI PEMBELAJARAN BIOLOGI UNTUK MENINGKATKAN KEBERMAKNAAN KONSEP DITINJAU DARI KEMAMPUAN INGATAN DAN KETELITIAN KERJA - ROSYIDI, ALVI (BIOEDUKASI, 2004)
The aim of this research were to study the influence of using the scientific method on these following aspect: (l) The lmprovement of concept of 4thsemester?s subject of Biological Education, FKIP UNS, (2) Whether the memory capabilities can be used as a predtictor or not (3) The Carefulness can be used as a significant predictor and (4) contribution of each predictor on that improvement. Descriptive quantitative research methods with expofacto were used. t test and regression were used to analyse the data. Data are collected by test method and lt's collection with two design; comparative and corelative on 30 samples of the 4th semester's student. The result showed that the scientific method could raise the improvement of subject concept only slightly with no statistical differences. Beside, there is a positive correlation between either the memory capabilities or carefulness and the improvement the concept, Key word:  Biological education with scientific method, lmprovement of concept ,memory capabilities